Evaluation of video streaming quality using quicktime streaming server (QTSS): a case study in Faculty of Information Technology & Quantitative Sciences, UiTM - Murli, Norhanifah (2005)
In a more broad definition, video streaming enables real-time or on-demand access to video files via local area networks or Internet. Video streaming files are stored in a streaming server, transferred and played back as it is downloaded by a client using a specific media player, leaving behind no residual copy of the content on the client's device. This teclmology enables users to view and hear digitized media content over a network without having to wait for the entire media files to be fully downloaded. Revolution in higher learning institutions was initiated by the emergence of video streaming. Streaming of media files perceived as a new tool to support and improve learning activities in academic environment. Many studies have indicated that video presentations are very resourceful and very attractive compared to text presentations. And it becomes even more interesting when these video files can be accessed and viewed real-time and on-demand by the students as an alternative way of revising their lecture content. Video streaming in education environment requires a very large storage, and can support delivery and playback to many simultaneous users that enables students to request for the video, and then play or stop or pause the digital content at their own convenience, without worrying of offending the lecturers. Through this dedicated link students can access learning materials such as lectures, pre-recorded tutorials and presentation anywhere and anytime in the campus network. To solve these issues, the implementation of video streaming application is very much needed. Realizing from this fact, this paper is written to discuss the implementation of video streaming applications in Fakulti Teknologi Maklumat dan Sains Kuantitatif, Universiti Teknologi MARA, Shah Alam and to investigate the video streaming quality that it has to offer. There are two methodologies used namely observation and literature search from previous researches. This paper also discusses the broad view of video streaming, streaming server system employed by the faculty, the format of video files supported by streaming server and its compression standard. In addition to this, issues faced by the streaming system are also investigated and finally some suggestions are made to the faculty to have a better v~deo streaming system implementation in the future.